The Influence of Australian Monsoon Winds on Simultaneous Occurrence of Mountain Waves in Central Java and East Java - Alpentido, Rahmat; Kristianto, Aries (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
Mountain waves are a phenomenon that had occurred due to the interaction of laminar flow in the atmosphere with the contours of the mountains. These waves had been characterized by the presence of lenticular clouds that had formed at the mountain peaks. On the 5th of November 2020, lenticular clouds had formed simultaneously in East and Central Java. During the same period, Australian Monsoon was still active in Java region. Based on these two phenomena, this research had investigated the influence of the Australian Monsoon on the process of mountain wave formation in Central Java and East Java using FNL data. The processing had been carried out using WRF-ARW with resolutions of 9, 3, and 1 km. The results had shown the presence of easterly winds that had affected the atmospheric stability of the Central Java and East Java regions, characterized by the formation of laminar flow, with the formation of laminar flow occurring first in the East Java region. The model output results for potential temperature parameters and visualizations had shown stable atmospheric conditions from the 4th to the 6th of November. The parameter of vertical wind speed had indicated the presence of mountain wave fluctuations in all regions.